Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

Small molecule inhibition of phosphatidylinositol-3,4,5-triphosphate (PIP3) binding to pleckstrin homology domains - Miao, Benchun; Skidan, Igor; Yang, Jinsheng; Lugovskoy, Alexey; Reibarkh, Mikhail; Long, Kai; Brazell, Tres; Durugkar, Kulbhushan A.; Maki, Jenny; Ramana, C. V.; Schaffhausen, Brian; Wagner, Gerhard; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The PI3-kinase (PI3K) pathway regulates many cellular processes, especially cell metabolism, cell survival, and apoptosis. Phosphatidylinositol-3,4,5-trisphosphate (PIP3), the product of PI3K activity and a key signaling molecule, acts by recruiting pleckstrin-homology (PH) domain-containing proteins to cell membranes. Here, we describe a new structural class of nonphosphoinositide small molecule antagonists (PITenins, PITs) of PIP3-PH domain interactions (IC50 ranges from 13.4 to 31 mu M in PIP3/Akt PH domain binding assay). PITs inhibit interactions of a number of PIP3-binding PH domains, including those of Akt and PDK1, without affecting several PIP2-selective PH domains. As a result, PITs suppress the PI3K-PDK1-Akt pathway and trigger metabolic stress and apoptosis. A PIT-1 analog displayed significant antitumor activity in vivo, including inhibition of tumor growth and induction of apoptosis. Overall, our studies demonstrate the feasibility of developing specific small molecule antagonists of PIP3 signaling.
Keywords: Anticancer; PIP3 antagonist

Optimization of the anti-cancer activity of the phosphatidylinositol-3 kinase pathway inhibitor PITENIN-1: switching thiourea with 1,2,3-triazole - Kommagalla, Yadagiri; Cornea, Sinziana; Riehle, Robert; Torchilin, Vladimir; Degterev, Alexei; Ramana, Chepuri V. (Medchemcomm, 2014)
We previously reported encouraging in vitro and in vivo anti-cancer activity of N-((3-chloro-2-hydroxy-5-nitrophenyl)carbamothioyl) benzamide (termed PITENIN-1). In the current work, we describe the structure-activity relationship study of the PIT-1 series, based on the replacement of a central thiourea unit with 1,2,3-triazole, which leads to increased liver microsomal stability, drug likeness and toxicity towards cancer cells.